2011
DOI: 10.1155/2011/820795
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Effects of Mineral-Oil Lubricant Contamination with Biofuels: A Pin-on-Disk Tribometry and Wear Study

Abstract: Use of biodiesel produces engine oil dilution because of unburned biodiesel impinging on cold walls of the combustion chamber, being scrapped to the oil pan, and leading to changes of oil friction, wear and lubricity properties. In this paper, mixtures of SAE 15W-40 oil, which were contaminated by known percentages of the biodiesels from canola oil, peanut oil, soybean oil, and chicken fat, were tested in a pin-on-disk tribometer. A contact was employed of AISI 1018 steel disk and AISI 316 stainless-steel ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Loss of lubricating oil alkalinity, which leads to corrosion and increased wear of engine parts, has also been demonstrated by the same study as a consequence of the use of biodiesel. Tests with soybean, canola, peanut and chicken fat biodiesel indicated that the negative impact of lubricating oil dilution by biodiesel on engine wear protection is not substantially different from the impact observed for operation with diesel oil . With regard to ethanol, no literature was found describing its interaction with engine lubricating oil.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of lubricating oil alkalinity, which leads to corrosion and increased wear of engine parts, has also been demonstrated by the same study as a consequence of the use of biodiesel. Tests with soybean, canola, peanut and chicken fat biodiesel indicated that the negative impact of lubricating oil dilution by biodiesel on engine wear protection is not substantially different from the impact observed for operation with diesel oil . With regard to ethanol, no literature was found describing its interaction with engine lubricating oil.…”
Section: Introductionmentioning
confidence: 99%
“…The amphiphilic nature of vegetable oils makes them effective for use in all three lubrication regimes, namely hydrodynamic, mixed, and boundary [11][12][13]. Several researchers are working on analysis and improvement of the friction properties of vegetable oils and their derived biolubricants for potential application as automotive lubricants [6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], metal working fluids [29][30][31][32], industrial fluid [33], food grade lubricant [34], chain saw, brake fluid, and transmission oil [35].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been undertaken to investigate the friction and wear properties of avocado oil [29], Calophyllum inophyllum oil [16], canola (rapeseed) oil [17,25,29,[36][37][38], coconut oil [26], corn oil [29], cotton seed oil [30], jatropha oil [13, 19-24, 31, 39], jojoba oil [12], Lunaria annua oil [40], olive oil [29], palm oil [6,15,18,22,28,34,41], peanut oil [25,29], rice bran oil [14], rubber tree seed oil [10,32], safflower oil [12,29], sesame oil [29], soybean oil [25,29,33,[42][43][44], and sunflower oil [27,43,45,46], or their chemically modified derivatives. Friction and wear behaviors of direct fatty acids derived synthetic esters have also been examined for their potential application as alternate lubricants [4,35,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…After the test this result of this work suggests that any degree of mineral oil dilution by the tested biodiesel can reduce the wear protection properties of the engine oil. [12] Khashaba et.al (2013) proposed polymeric composites are consisting of polyethylene (PE), polypropylene (PP) and polystyrene (PS) and filled with fibers of polytetra fluoroethylene, and (PTFE) in concentration up to 25 wt. % as well as different types of natural oils such as (corn oil, olive oil, paraffin oil, glycerin oil, castor oil and sunflower oil) in concentration up to 10 wt.…”
Section: Introductionmentioning
confidence: 99%